Analysis of the legal evolution of medical practice in Colombia - Galán Camargo, Viviana (DIXI, 2019)
Purpose: The purpose of this research is to illustrate the problem of impunity in Colombia. The focus is on cases of medical responsibility for failures in the provision of health services, through a study that will bring together sociological, legal and statistical aspects, and at the same time it will discuss the evolution of jurisprudence in the field of health as a fundamental right and as a service provided by the state. Methodology: The lex artis will be analyzed from the scientific aspect of the law and from some points of view with a scientific, philosophical of technique and art tendency. At the same time, these points of view will be applied in contrast to the legal activity, in order to understand to some extent the legal practice with respect to the medical activity, within the legal referential framework established for the ethical behavior of the health professional. Findings: Through the analysis of the concepts of interference or criteria to be taken into account in the legal assessment of the medical case, such procedure will be studied, which seeks to organize and understand the structure of legal activity in the specific case. Conclusions: The doctor-patient relationship and the legal problems that arise between them are a consequence of the absence of clear and concrete legal regulation of the actions that derive from medical practice, in which this is only a part of the financial activity of the health sector.